Desenvolvimento e caracterização de nanopartículas de quitosana/PLA contendo própolis para aplicações biomédicas - Pereira, Kevin Johnson Gonçalves (2020)
The present study aimed to synthesize different formulations of propolis-loaded chitosan and polylactic acid (PLA) nanoparticles through the nanoprecipitation method for biomedical applications. The association of propolis to the nanoparticles can bring some interesting results, due to its antibacterial, antioxidant, anti-inflammatory activities. Propolis was characterized by Fourier-transformed Infrared Spectroscopy (FTIR) and submitted to the colorimetric method to determine the total flavonoids content. The nanoparticles (non-loaded and loaded) were characterized by Dynamic Light Scattering (DLS), Zeta Potential (at different pH values), FTIR and Scanning Electronic Microscopy (SEM). Assays were performed to evaluate encapsulation efficiency of propolis and the in vitro release profile of nanoparticles. Finally, the nanoparticles antimicrobial activity by disk-diffusion method and Minimum Inhibitory Concentration (MIC) by microdilution were also evaluated, both tests were performed against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative). In Zeta Potential as function of pH, it was observed that nanoparticles present mostly positive charges, such result is interesting for cell adhesion of the nanoparticles. Through FTIR analysis, was possible to analyze propolis components and it was also found that the characteristic bands of the isolated compounds reappeared in the nanoparticles, indicating that propolis incorporation was successful. The MEV results showed that the particles size is close to the values obtained through DLS (between 180 and 890 nm), it was also found that the nanoparticles were properly formed, however, with some irregularities in their shape. The propolis entrapment efficiency of the samples ranged from 76 to 89%. The release study showed an initial burst release in the first 24 hours, this result is interesting for applications such as wound treatment. In antimicrobial evaluation and MIC, the propolis-loaded nanoparticles with the highest chitosan content in the composition showed the highest antibacterial activity, this result were valid for both strains. The results suggest that propolis-loaded chitosan/PLA nanoparticles are promising drug delivery systems for biomedical applications.